Edukasi dan Pemeriksaan Kesehatan Di Wilayah Pimpinan Cabang Asiyiyah Cengkareng - Asti Al Hikmah; Ibnu Salis Fitra; Mellisa Kasim; Muhammad Hendrawan Ramadhani; Refina Oktavia (Pusat Riset dan Inovasi Nasional, 2024)
Increased life expectancy and behavioral changes and demographic transitions trigger epidemiological transitions. The World Health Organization (WHO) declared 2020-2030 the